Whitefly‐induced tomato volatiles mediate host habitat location of the parasitic wasp Encarsia formosa, and enhance its efficacy as a bio‐control agent. Issue 2 (18th September 2020) - Chen, Chan‐Shan; Zhao, Chan; Wu, Zhi‐Yi; Liu, Guang‐Fu; Yu, Xiao‐Ping; Zhang, Peng‐Jun
Abstract: BACKGROUND: Whitefly Bemisia tabaci is a phloem‐feeding insect and causes extensive agricultural damage around the world. Although the parasitic wasp Encarsia formosa is widely used to control B. tabaci on glasshouse tomatoes, low efficiency and discontinuity are frequently recorded. It has been well‐documented that herbivore‐induced plant volatiles (HIPVs) are important cues in the foraging behavior of the natural enemies of herbivores. However, the volatiles emitted from tomatoes infested by different developmental stages of B. tabaci (nymphs versus adults) have not been compared in terms of their effects on E. formosa attraction. RESULTS: Olfactometer assays with four tomato cultivars revealed that the E. formosa wasps showed a significant attraction to the volatiles from adult‐infested plants (except for cv. Castlemart), but not to those from nymph‐infested plants. In a close‐range habitat, however, the wasps appeared to use visual or tactile cues derived from nymphs for host location. Volatile analyses and behavioral assays showed that wasp attraction was correlated with enhanced β ‐myrcene and β ‐caryophyllene emissions from adult‐infested plants. Furthermore, the use of B. tabaci adult‐induced plant cues under glasshouse conditions resulted in a higher parasitism rate by this parasitoid. CONCLUSION: Our findings confirm that E. formosa uses the HIPVs resulting from feeding of B. tabaci adults to locate host habitat. Release of β ‐myrcene and β ‐caryophyllene from dispensers may enhance the efficacy of E. formosa as a biological control agent against B. tabaci in glasshouse production systems. Abstract : This study shows that the parasitic wasp Encarsia formosa uses the herbivore‐induced plant volatiles (HIPVs) resulting from feeding of Bemisia tabaci adults to locate host habitat. Release of β ‐myrcene and β ‐caryophyllene from dispensers may enhance the efficacy of E. formosa as a biological control agent against B. tabaci in glasshouse production systems. © 2020 Society of Chemical Industry